Effect of tillage and moisture-conservation practices on productivity, water use and water-use efficiency of pearl millet (Pennisetum glaucum) on light soils under dryland condition - SINGH, SAUDAN; KAUSHIK, S K; GAUTAM, R C (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during the rainy season (kharif) of 1989 and 1990 to study the effect of deep summer tillage with and without incorporation of farmyard manure and soil mulching on grain yield, water use and water-use efficiency of pearl millet [Pennisetum glaucum (L.) R. Br. emend. Stuntz]. Pearl millet yield vluied significantly due to tillage practices only in 1990. The highest grain yield (2.25 tonnes/ha) was obtained with no summer ploughing and lowest (1.52 tonnes /ha) with chiselling + deep summer ploughing + farmyard mauure. Seasonal water use was highest with no summer :ploughing in both the years. Water-use efficiency was highest (10. 4l kg grain/ha-mm) with chiselling + deep summer ploughing + farmyard manure in 1989, and with no summer ploughing (6.0 kg grain/ha/mm) in 1990. Net return was highest (Rs 4 313 kg/ha) with deep summer ploughing + frumyard manure in 1989 and with no summer ploughing (Rs 4 852/ha) in 1990. However, net return/rupee invested was highest with no summer ploughing in both the years, being Rs 1.45 and 1.67 in 1989 and 1990 respectively. Soil mulching showed beneficial effect on yield only in 1989. The highest grain yield (2.30 tonnes/ha) was obtained with dust mulch, closely followed by straw mulch (2.18 tonnes/ha). Soil mulching caused considerable increase in water use and water-use eniciency only in 1989. Though dust mulch resulted in higher seasonal waler use than straw mulch, there was no marked difference between these 2 for water use effciency. Net return (Rs 4 601/ha) as well as net return/rupee invested (Rs 1.32) were highest with dust mulch in 1989. However, net retum (Rs 5 965/ha) and net return/rupee invested (Rs 1.36) were highest with no mulch in 1990.